Knowledge, Attitude and Practice of Tooth Morphology among the Dentists of Kathmandu - Chaulagain, Rajib (Journal of Nepalese Prosthodontic Society, 2019)
Background: Dental anatomy is taught as a basic dental subject in dental schools of Nepal. The knowledge has immense use in clinical practice in dentistry. However, few people feel that it has no use and should be removed from the dental curriculum. The objective of the study was to analyze the knowledge, attitude and practice of tooth morphology among dental practitioners in Kathmandu.Materials and Methods: A cross-sectional study was undertaken among the dental practitioners in Kathmandu using a self-administered questionnaire to collect the data. In total 300 questionnaires were distributed. The results were analysed for descriptive statistics using the Statistical Package for the Social Sciences (SPSS) 16 software.Results: A total of 249 responses from the dental practitioners were received. In total 77.9 % of participants strongly agreed that understanding tooth morphology helped in identification of primary and permanent teeth. More than 90% had positive response regarding its use in day to day clinical practice.Conclusion: The present study revealed that the dental practitioners have adequate knowledge of tooth morphology and agree on its importance in professional dental practice.